The history of alcoholic liver disease: from an unrecognized disease to one of the most frequent diseases in hepatology - Seitz, Helmut K.; Neuman, Manuela G. (Journal of Clinical Medicine, 2021)
This review describes the history of alcoholic liver disease from the beginning of the 1950s until now. It details how the hepatotoxicity of alcohol was discovered by epidemiology and basic research primarily by using new feeding techniques in rodents and primates. The article also recognizes the pioneering work of scientists who contributed to the understanding of the pathophysiology of alcoholic liver disease. In addition, clinical aspects, such as the development of diagnostics and treatment options for alcoholic liver disease, are discussed. Up-to-date knowledge of the mechanism of the disease in 2020 is presented.